1996
DOI: 10.1007/bf00054849
|View full text |Cite
|
Sign up to set email alerts
|

Within-tree variability of mountain birch leaves causes variation in performance for Epirrita autumnata larvae

Abstract: Within-tree variability in leaf characteristics of the mountain birch (Betula pubescens ssp. tortuosa) was bioassayed for the autumnal moth (Epirrita autumnata) by rearing larvae on birch leaves in a laboratory and measuring their growth, consumption rate, approximate digestibility, efficiency of conversion of ingested food and efficiency of conversion of digested food. Only short shoot leaves, i.e. leaves of the same age, were used. The highest hierarchical level, which included trees and ramets within trees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Therefore, nutrient-induced increases in leaf size (and probably nutritional content) together with decreases in secondary chemistry could enhance the growth of herbivores in those sectors. Suomela and colleagues have shown that the growth of Epirrita autumnata (Geometridae) larvae varies by as much as 30% within a single birch tree (Suomela and Nilson, 1994;Suomela, Kaitaniemi, and Nilson, 1995;Suomela, 1996). Perhaps some of this variation is due to belowground variation in nutrient availability.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, nutrient-induced increases in leaf size (and probably nutritional content) together with decreases in secondary chemistry could enhance the growth of herbivores in those sectors. Suomela and colleagues have shown that the growth of Epirrita autumnata (Geometridae) larvae varies by as much as 30% within a single birch tree (Suomela and Nilson, 1994;Suomela, Kaitaniemi, and Nilson, 1995;Suomela, 1996). Perhaps some of this variation is due to belowground variation in nutrient availability.…”
Section: Discussionmentioning
confidence: 94%
“…Heterogeneity in resource quality can affect herbivores by changing their foraging behavior, growth, survival, fecundity or dispersal and may ultimately affect population dynamics (Denno and McClure 1983and references therein, Caine et al 1985, Barbosa 1988, Price 1991, Schultz 1992, Waring and Cobb 1992, Barker et al 1995, Belovsky and Joern 1995, Denno and Peterson 1995, Hunter and Price 1995, Suomela 1996, Karban and Baldwin 1997. Several studies have demonstrated the importance of within-plant heterogeneity to leaf-chewing herbivores (Schultz 1983, Edwards et al 1985, Suomela and Ayres 1994, Suomela and Nilson 1994, Barker et al 1995, Suomela et al 1995.…”
Section: Herbi6oresmentioning
confidence: 99%
“…Several studies have demonstrated the importance of within-plant heterogeneity to leaf-chewing herbivores (Schultz 1983, Edwards et al 1985, Suomela and Ayres 1994, Suomela and Nilson 1994, Barker et al 1995, Suomela et al 1995. For example, Suomela and Ayres (1994) compared within-tree and among-tree variation in birch leaf characteristics and observed that 40-44% of the variation in water content, specific weight and toughness was found within a birch tree, and that the growth of Epirrita autumnata (Geometridae) larvae varied by as much as 30% within a single tree (Suomela and Nilson 1994, Suomela et al 1995, Suomela 1996. Within-plant variation is often attributed to differences in leaf developmental stage or leaf initiation rate (e.g.…”
Section: Herbi6oresmentioning
confidence: 99%
“…Birch is recognised as being temporally and spatially heterogeneous in terms of resource quality for herbivores (Suomela, 1996; Suomela et al ., 1997). For instance, the quality of birch leaves eaten by chewing insects declines rapidly within a single season (Hanhimäki et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%